2001
DOI: 10.1521/psyc.64.1.69.18236
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Cope Better Than Adults with Potentially Traumatic Stress? A 40-Year Follow-Up of Holocaust Survivors

Abstract: Anecdotal reports suggest that child survivors of the Nazi persecution are functioning well as adults. Ratings of their parents by a randomly selected community sample of young adult Ashkenazi Jews on a scale that measured Schizoid, Paranoid, Depressive/Masochistic and Type A/Normal Aggressive symptoms permitted verification of these reports. Among the parents were groups who were children, adolescents, or young adults in 1945, at the end of World War II. Child-survivor parents did not differ from native-born … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 34 publications
1
21
0
2
Order By: Relevance
“…Consistent with the present findings, Green et al (1991) found that fewer preschool children than school children developed PTSD. Studies on people who survived Holocaust as children have shown positive correlations between age and traumarelated distress later in life (e.g., Sigal & Weinfeld, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the present findings, Green et al (1991) found that fewer preschool children than school children developed PTSD. Studies on people who survived Holocaust as children have shown positive correlations between age and traumarelated distress later in life (e.g., Sigal & Weinfeld, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Sigal and Weinfeld (2001) found that Holocaust survivors who had been between 2 and 13 years old at the time the war ended scored lower on a number of measures of psychological distress than survivors who had been 14 to 24 years old by the end of the war. Cohen et al (2003) examined PTSD symptoms among 134 Holocaust survivors.…”
Section: Empirical Studies Of Age In Relation To Ptsdmentioning
confidence: 94%
“…Cet article a également donné un aperçu de la littérature sur les effets engendrés par les mauvais traitements subis par les personnes institutionnalisées en bas âge (Rutter et al, 1999 ;Morrison et al, 1995 ;O'Connor et al, 2000 ;Johnson et al, 2006) ainsi que sur les facteurs de protection (Matussek, 1975 ;Sigal et al, 1999 ;Sigal et Weinfeld, 2001 ;Shmotkin, 2003). Ce deuxième article met l'accent sur les résultats qualitatifs recueillis à l'aide d'entrevues semi-structurées destinées à documenter les expériences, tant actuelles que passées, des EDI.…”
Section: Contexte Théoriqueunclassified
“…D'autre part, les caractéristiques personnelles des enfants font en sorte que certains d'entre eux feront mieux face à des situations de privation et de stress extrêmes sans conserver des séquelles psychologiques et physiques majeures à l'âge adulte (Eaton et al, 1982 ;Shmotkin, 2003). Ainsi, la documentation scientifique sur la résilience permet d'identifier les facteurs familiaux (Matussek, 1975), les habiletés cognitives (Sigal et al, 1998), le style défensif et les capacités d'adaptation (Shmotkin, 2003 ;Sigal et Weinfeld, 2001) comme des facteurs pouvant aider les enfants institutionnalisés à faire face à l'adversité. Les expériences d'abus, les expériences d'attachement et les caractéristiques personnelles sont donc trois domaines qui peuvent aider à comprendre le cheminement de vie des Orphelins.…”
unclassified